A review of carbon fiber surface modification methods for tailor-made bond behavior with cementitious matrices. (February 2023) - Li, Huanyu; Liebscher, Marco; Zhao, Dong; Yin, Bo; Du, Yuhang; Yang, Jian; Kaliske, Michael; Mechtcherine, Viktor
Abstract: Insufficient bonding behavior between intrinsically hydrophobic carbon fibers and water-based suspensions restricts the application of carbon fiber (CF) reinforced cements and other mineral building materials. To resolve this issue several researchers have investigated physical and chemical modification methods for enhanced load transfer from mineral matrices to CFs. Polymer impregnations and temperature-stable mineral suspensions have been used to tailor the interphase zone between CF rovings and surrounding matrices, achieving, e.g ., better pullout behavior. Additionally, surface modification approaches such as oxidation, electrophoretic deposition, plasma, and grafting treatments as well have been applied to improve fiber–matrix interactions. In this article these approaches are systematically reviewed and compared to describe and recommend appropriate methods for achieving tailor-made interfacial bonding behavior. Finally, suitable approaches to characterization are discussed to provide a comprehensive overview of the related methodology and to assist in studying the characteristics of the carbon fiber itself and its bonding behavior toward mineral matrices.